2023
DOI: 10.21203/rs.3.rs-2579263/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for the formation of fused aromatic ring structures in an organic soil profile in the early diagenesis

Abstract: The presence of fused aromatic ring (FAR) structures in soil define the stability of the recalcitrant soil organic matter (RSOM). FAR are important skeletal features in RSOM that contribute to its extended residence time. During the early diagenesis, FAR are formed through condensation and polymerization of biomolecules produced during plant residue and microbial product decay. Molecular level characterization of the RSOM extracted from an organic soil profile gives important insights into the formation of FAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…28,29 Another recent study observed non-pyrogenic formation of ConAC in the aerobic microbial incubation of wheat straw, 30 an example of a microbiological system where microbes exude extracellular enzymes, which release ROS. These mechanistic studies explain the observation of nonpyrogenic ConAC formation during soil humification 31 and photochemical DOC irradiation. 26 However, due to the use of qualitative (electrospray ionization−mass spectrometry) or less conventional methods (spectral editing nuclear magnetic resonance (NMR) spectroscopy) in these studies, their results "warrant further investigation using quantitative methods such as the benzenepolycarboxylic acids (BPCA) method [sic]".…”
Section: ■ Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…28,29 Another recent study observed non-pyrogenic formation of ConAC in the aerobic microbial incubation of wheat straw, 30 an example of a microbiological system where microbes exude extracellular enzymes, which release ROS. These mechanistic studies explain the observation of nonpyrogenic ConAC formation during soil humification 31 and photochemical DOC irradiation. 26 However, due to the use of qualitative (electrospray ionization−mass spectrometry) or less conventional methods (spectral editing nuclear magnetic resonance (NMR) spectroscopy) in these studies, their results "warrant further investigation using quantitative methods such as the benzenepolycarboxylic acids (BPCA) method [sic]".…”
Section: ■ Introductionsupporting
confidence: 66%
“…The lack of correlation is consistent with our proposition that ConAC in soil is primarily derived from a non-pyrogenic process, which has been also shown empirically recently. 31 Furthermore, ConAC is strongly correlated with SOC regionally 18 −21 and globally 8,22 (Figure 5B). The current interpretation for this ConAC-SOC correlation is that charcoal from ancient fires (referred to as legacy BC) is equally distributed globally in SOC pools.…”
Section: Samplesmentioning
confidence: 90%
See 2 more Smart Citations